Insidious Assumptions: How Pluralistic Ignorance of Studying Behavior Relates to Exam Performance. (October 2018) - Buzinski, Steven G.; Clark, Jenna; Cohen, Matthew; Buck, Benjamin; Roberts, Scott P.
Pluralistic ignorance occurs when individuals misperceive a group norm and attempt to match the perceived—rather than actual—norm. Little is currently known about its role in the undergraduate classroom. The present research examined the pluralistic ignorance of studying behavior and its relationship with examination performance across four studies. Results suggested that students underestimate the amount of time their peers spend studying (Study 1), the extent of their estimation error is related to exam performance (Study 2), and that the relationship is mediated by a perceived lack of preparation (Study 3). Finally, a brief classroom intervention (Study 4) may be able to eliminate the pluralistic ignorance. Implications for the theory of pluralistic ignorance, and college teaching, are discussed.